The key factors impacting on ccience communication effects in the WeChat official accounts: A theoretical framework of risk-benefit perceptions - Panqiang Niu; Caixie Tu; Maria Efiyana; Liu Jian; Anang Masduki (Universitas Negeri Yogyakarta, 2023)
By adopting the theoretical framework of Risk-Benefit perceptions, this study takes the popularization of Artificial Intelligence (AI) knowledge as an empirical object to test the key factors impacting on science communication effects in the WeChat official accounts. Results showed that science communication uncertainty produced both direct and indirect effects on science communication effects. The indirect effect was mainly mediated by perceived risk. Public trust negatively moderated the association between perceived uncertainty and perceived risk at a low trust level. Perceived entertainment had a positive effect on science communication effects in the benefit-perception perspective.